Manipulation of playing field`s length/width ratio and neutral players` positioning: activity profile and motor behavior demands during positional possession soccer small sided games in young elite soccer players - Gollin, M.; Alfero, S.; Abate Daga, F. (International Journal of Sports Science, 2016)
This study aimed to examine how changes in pitch length/width ratio and neutral players' positioning could modify the activity profile and motor behaviour demands during small-sided positional possession soccer games. 22 young male elite players divided in 2 teams (A and B) of 11 players participated in the study. All players participated in a positional possession game (4-a-side + 3 neutral players) on two different pitch formats with opposite length/width ratios (WIDE: 25 x 35 m; LONG: 35 x 25 m) and two different kinds of positioning for neutral players (VERTICAL: positioned high; HORIZONTAL: wide). The time motion variables of each player were recorded using a 15 Hz portable GPS. Average player displacement in width was significantly higher in WIDE format, while average player displacement in depth was significantly greater in LONG format (p < .001). Moreover, an increased activity profile was observed in regular team players with respect to neutral players (p < .001). These results highlight the physical and motor behaviour demands in small sided positional possession games. Furthermore, the different physical tasks required by various pitch formats and player positions were underlined. This information can help coaches to set up game-based training sessions.